Assessment of Background Gamma Radiation Level in Selected Dump Site of Niger Delta, Nigeria - , C. D. Anyalebechi; , O. L. Gbarato; , C. P. Ononugbo (Archives of Current Research International, 2022)
Our environment has been exposed to ionizing radiation from indiscriminate dumping of refuse which is seen as unending and unpreventable challenge on earth. Radiation level and exposure risks in some selected dump site in Rivers state have been calculated using radiation exposure rate meter (Radalert-100). Rate of exposure measured at Ignatius Ajuru University of Education (IAUE) and its environment ranged from 0.005±0.0001 to 0.016±0.003 mRh-1 with mean value of 0.015±0.002 mRh-1 and that measured at Igwuruta ranged from 0.009±0.001 to 0.048±0.003 mRh-1 its mean value is 0.015±0.002 mRh-1. For All, the exposure rate measured ranged from 0.009±0.0001 to 0.015±0.002 mRh-1 its mean value is 0.012±0.004 mRh-1. The exposure rates measured in the three dump site are relatively equal and slightly higher than the recommended permissible limit of 0.013 mRh-1. Estimation of the mean absorbed doses from the exposure rates for Ignatius Ajuru University of Education, Igwuruta and Aluu are 127.72±31.26, 125.91±18.35 and 175.64±41.61 nGyh-1 respectively, its mean absorbed doses are 1.16, 1.18 and 1.11 mSvy-1 respectively. The annual effective dose equivalent calculated is 0.20±0.03, 0.19±0.03 and 0.19±0.03 mSvy-1. The excess lifetime cancer risk estimated ranged from 0.68±0.11, 0.68±0.10 and 0.68±0.10 respectively, they are all above the recommended values 0.29x10ˉ3 in all the sampling locations. Following the result from the radiation level of the dump site, no immediate radiation risk is expected, but there could be a long term effects on those living around the dump side.